First total synthesis of hoshinoamide A - Zhou, Haipin; Rui, Zihan; Yang, Yiming; Xu, Shengtao; Shao, Yutian; Liu, Long (Beilstein Journal of Organic Chemistry, 2021)
Hoshinoamides A, B and C, linear lipopeptides, were isolated from the marine cyanobacterium Caldora penicillata, with potent antiplasmodial activity against chloroquine-sensitive Plasmodium falciparum. Herein, we describe the first total synthesis of hoshinoamide A by the combination of liquid-phase and solid-phase peptide synthesis. Liquid-phase synthesis is to improve the coupling yield of ʟ-Val3 and N-Me-ᴅ-Phe2. Connecting other amino acids efficiency and convergence is achieved by solid-state synthesis. Our synthetic strategy could synthesize the target peptide in high yield with good purity
Keywords: antimalarial; highly methylated polypeptides; hoshinoamides; total synthesis